Cervical vestibular evoked myogenic potentials in healthy children: Normative values for bone and air conduction - Wiener-Vacher, Sylvette R.; Campi, Marta; Boizeau, Priscilla; Thai-Van, Hung (Frontiers in Neurology, 2023)
Objectives: To characterize cervical vestibular evoked myogenic potentials (c-VEMPs) in bone conduction (BC) and air conduction (AC) in healthy children, to compare the responses to adults and to provide normative values according to age and sex. Design: Observational study in a large cohort of healthy children (n=118) and adults (n=41). The c-VEMPs were normalized with the individual EMG traces, the amplitude ratios were modeled with the Royston-Wright method. Results: In children, the amplitude ratios of AC and BC c-VEMP were correlated (r= 0.6, p<0.001) and their medians were not significantly different (p=0.05). The amplitude ratio was higher in men than in women for AC in children (p=0.04) and BC (p=0.01). Children had significantly higher amplitude ratios than adults for AC (p=0.01) and BC (p<0.001). Normative values for children are shown: - Amplitude ratio is age-dependent for AC more than for BC - Confidence limits of interaural amplitude ratio asymmetries were less than 35% - Thresholds were not different between AC and BC (88±5 and 86±6 dB nHL, p=0.99) - Mean latencies for AC and BC were for P-wave 13.0 and 13.2 msec and for N-wave 19.3 and 19.4 msec. Conclusions: The present study provides age- and sex-specific normative data for c-VEMP for children (6 months to 15 years of age) for AC and BC stimulation. Up to the age of 15 years, c-VEMP responses can be obtained equally well with both stimulation modes. Thus, BC represents a valid alternative for vestibular otolith testing, especially in case of air conduction disorders.